Development of a Piglet Grimace Scale to Evaluate Piglet Pain Using Facial Expressions Following Castration and Tail Docking: A Pilot Study - Viscardi, Abbie V.; Hunniford, Michelle; Lawlis, Penny; Leach, Matthew; Turner, Patricia V. (Frontiers in Veterinary Science, 2017)
Facial expressions are increasingly being used to assess pain in non-human species, including rodents, horses and lambs. The development of these species-specific grimace scales have allowed for more rapid pain detection, which can lead to better animal welfare if intervention promptly occurs. For grimace scales to ever be used as a stand-alone measure of pain, it is important they correlate with established pain assessment tools, such as behavioral analysis. This preliminary study aimed to determine whether piglets exhibit pain grimacing and if these facial expressions correlate with their behavior. It also assessed and compared the behavior of boar piglets given an analgesic and topical anesthetic prior to surgical castration and tail docking to piglets that did not receive anything for pain relief. Five-day-old male Yorkshire piglets (n = 19) from four pens were randomly assigned, within their pen, to one of five possible treatments: meloxicam (0.4mg/kg, intramuscularly) + EMLA® cream, meloxicam (0.4mg/kg, intramuscularly) + non-medicated cream, saline (intramuscularly) + EMLA® cream, saline (intramuscularly) + non-medicated cream or no treatment prior to surgical castration and tail docking. Piglet behaviors were video recorded for 8h immediately after castration, as well as for 1h at 24 hours pre- and post-castration. Their individual behaviors were scored continuously for the first 15mins of every hour of video collected. Facial images were also captured across all time points. A Piglet Grimace Scale (PGS) was developed and used by two observers blinded to treatment, time and procedure to score over 600 piglet faces. All piglets displayed significant behavioral changes up to 7h post-castration when compared to baseline, and the use of meloxicam and EMLA® cream was not associated with a reduction in painful behaviors. Significantly higher PGS scores were noted at 0, 3, 4, and 5h post-castration when compared to PGS scores at 7h and there was no effect of treatment. PGS scores significantly correlated with piglet behavioral activity. The results suggest that the Piglet Grimace Scale may have utility for pain evaluation in neonatal pigs.